2020
DOI: 10.3390/app10228081
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and Genetic Biomarkers of Choroidal Melanoma

Abstract: Choroidal melanoma (CM), despite its rarity, is the most frequent intraocular malignancy. Over time, several histological variants of CM have been distinguished, including spindle A and B cell, fascicular, epithelioid and necrotic type. However, they have been progressively abandoned as having no prognostic value and currently, the American Joint Committee of Cancer (AJCC) classification identifies three CM cell types: spindle, epithelioid and mixed cell type. Other rare histological variants of CM include: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…It would be desirable to have noninvasive markers that may predict a tumor's response to therapy and provide prognostic information. A biopsy is an invasive procedure and may not always be representative because chromosomal aberrations can be heterogeneous across the tumor [35,36] Both the presence of monosomy 3 [22,37,38] and of extracellular matrix patterns "loops" [39][40][41][42][43][44] are important determinants of poor prognosis and they frequently coexist. All our tumors with loops had monosomy 3 and vice versa, consistent with the literature where monosomy 3 is detected in 67% of tumors with loops [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be desirable to have noninvasive markers that may predict a tumor's response to therapy and provide prognostic information. A biopsy is an invasive procedure and may not always be representative because chromosomal aberrations can be heterogeneous across the tumor [35,36] Both the presence of monosomy 3 [22,37,38] and of extracellular matrix patterns "loops" [39][40][41][42][43][44] are important determinants of poor prognosis and they frequently coexist. All our tumors with loops had monosomy 3 and vice versa, consistent with the literature where monosomy 3 is detected in 67% of tumors with loops [40].…”
Section: Discussionmentioning
confidence: 99%
“…Both the presence of monosomy 3 [ 22 , 37 , 38 ] and of extracellular matrix patterns “loops” [ 39 44 ] are important determinants of poor prognosis and they frequently coexist. All our tumors with loops had monosomy 3 and vice versa, consistent with the literature where monosomy 3 is detected in 67% of tumors with loops [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential identification of a high-risk group of patients could allow the performance of more frequent controls in order to earlier diagnose cases with liver metastases that could be safely surgically excised [30]. Accordingly, in the last decade our research group reported some novel potential immunohistochemical factors with prognostic impact [5,[31][32][33][34][35], which may be included into the list of the classically reported markers of UM, such as tumor location, tumor size, extraocular invasion, cell type, pathological T stage and immunohistochemical staining with BAP1 [14]. Recently, Luo et al identified a ten-gene signature (SIRT3, HMCES, SLC44A3, TCTN1, STPG1, POMGNT2, RNF208, ANXA2P2, ULBP1 and CA12), able to better stratify the outcome of UM patients [36]; in detail, ANXA2P2, ULBP1, CA12 had a poor prognostic role, while the other genes a positive one.…”
Section: Discussionmentioning
confidence: 99%
“…UM is a slow-growing tumor with indolent biological behavior but consistently poor prognosis, characterized by the development of liver metastases within 10-15 years after the diagnosis in about 50% of cases [6][7][8][9]. In recent years, the search for genetic and epigenetic prognostic and/or predictive factors of therapeutic response has been one of the most studied topics in cancer research [10,11]; in this regard, loss-of-function mutations of BRCA1 associated protein-1 (BAP1), that have been observed in most metastasizing UM cases and correlated with the immunohistochemical loss of BAP-1 protein, represent one of the most reliable prognostic factors of this tumor [12][13][14]. Serine and arginine-rich splicing factor 1 (SRSF1) is part of the SR protein family, being involved in canonic and alternative pre-mRNA splicing and in the regulation of mRNA transcription [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…From a histologic point of view, uveal melanoma can be pigmented, amelanotic or mixed [ 8 , 9 ]; the lesion is generally solid, though necrotic or hemorrhagic areas may occur as well. Necrosis, in particular, may produce cystic spaces or storage of eosinophilic debris within the neoplasm [ 10 ].…”
Section: Introductionmentioning
confidence: 99%